1997
DOI: 10.3109/10715769709097838
|View full text |Cite
|
Sign up to set email alerts
|

Hemin-Induced Membrane Sulfhydryl Oxidation: Possible Involvement of Thiyl Radicils

Abstract: Sublytic levels (microM) of hemin destabilized RBC membrane as indicated by ghost fragmentation pattern using a laser viscodiffractometer. Furthermore, electron microscopic study shows that 5 microM of hemin induced echinocytic transformation whereas higher hemin concentration (40 microM) induced spherocytic transformation. In addition, hemin oxidized sulfhydryl groups in a dose dependent fashion and Electron Spin Resonance study suggests that such oxidation may involve a thiyl radical. Moreover, sulfhydryl co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 28 publications
1
11
1
Order By: Relevance
“…Alteration of cell shape after the hemin action, i.e. formation of echinocytes and spheroechinocytes, was detected by a light microscopy7. However, this approach does not allow to show the grain-like structures on the cell membrane.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alteration of cell shape after the hemin action, i.e. formation of echinocytes and spheroechinocytes, was detected by a light microscopy7. However, this approach does not allow to show the grain-like structures on the cell membrane.…”
Section: Resultsmentioning
confidence: 99%
“…The objects of its action in RBC are known. The optical microscopy and electron microscopy showed that hemin causes a formation of echinocytes under low concentrations and spheroechinocytes under high concentrations7. Finally this leads to hemolysis.…”
mentioning
confidence: 97%
“…Second, denaturation of hemoglobin (Hb) can cause the damage. Accumulating evidence has shown that released hemin, one of the end product of Hb denaturation, is a potent catalyst of lipid peroxidation, which in turn causes hemolysis [27][28][29]. Many microscopy studies have shown that hemin can affect the conformation of the cell cytoskeleton, which in turn affects the cell structure [27,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, to promote lipid peroxidation, hemin could affect RBC morphology and destabilize membrane [12], Further study indicated that hemin could oxidize membrane sulfhydryl groups in a dose-dependent fash ion. Our electron spin resonance study suggested that such oxidation may be mediated by a thiyl radical.…”
Section: Introductionmentioning
confidence: 99%
“…Our electron spin resonance study suggested that such oxidation may be mediated by a thiyl radical. Desferroxamine could prevent hemin-induced sulfhydryl oxi dation as well as hemin-induced decrease in membrane stability [12].…”
Section: Introductionmentioning
confidence: 99%